2012
DOI: 10.1093/hsw/hls025
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Determining the Experience of Blindness among Pregnant Women in Developing Countries: The Case of India

Abstract: Approximately 10 million pregnant women around the world develop night blindness annually. In India, one in 11 pregnant women suffers from night blindness. This study used a nationally representative sample of 35,248 women from India between the ages of 15 and 49 who had given birth in the past five years to understand the effect of women's empowerment on developing blindness during pregnancy. Findings from logistic regression showed that several empowerment-related factors, including women's increased age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In a study of 120 pregnant women in the USA with spinal cord injury, 56% reported that their local hospital could not accommodate their disability needs when they gave birth [37]. Similar findings emerged in a large nationally representative survey of pregnant women (n = 35,248) across India [38]. Of the women experiencing pregnancy related blindness (12%), nearly 60% reported that they were concerned about the quality of maternity services.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In a study of 120 pregnant women in the USA with spinal cord injury, 56% reported that their local hospital could not accommodate their disability needs when they gave birth [37]. Similar findings emerged in a large nationally representative survey of pregnant women (n = 35,248) across India [38]. Of the women experiencing pregnancy related blindness (12%), nearly 60% reported that they were concerned about the quality of maternity services.…”
Section: Resultsmentioning
confidence: 78%
“…Eight studies highlighted barriers which compromise access to maternity care [35,37,38,40-42,44,45], relating to: mental health diagnosis; poor relationships with health professionals; environmental barriers; domestic abuse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the prevalence of XN can also indicate nutritional deficiency due to, for example, acute changes in living conditions, economic crises or reduction in employment rates, which affect the prevalence of XN in pregnant women and pre-school children (15) . Inadequate dietary intake of vitamin A is the most recognized risk factor for VAD (2,8,(16)(17)(18) . However, other factors need to be further studied, such as lack of education, poor sanitation, food insecurity, low maternal socioeconomic status, poorly diversified and plant-based diets and low consumption of vitamin A-rich foods, whose association with VAD has been well described in studies conducted in Asia and Africa (16,19,20) .…”
mentioning
confidence: 99%